Predictive Role of Narcissism and Family Relations on Decision-making Characteristics of Secondary School Students - ÜMMET, DURMUŞ; EKŞİ, HALİL (ANI YAYINCILIK, 2019)
Purpose: This study aimed at examining the effects of narcissism and family relations on secondary school students' decision-making characteristics. The study also investigated whether or not students' decision-making characteristics differentiated according to gender. Research Methods: Participants were secondary school students who were studying at different secondary schools in Istanbul, and who were selected randomly on a voluntary basis. Formed by a relational screening model, data were collected using the Adolescent Decision-Making Questionnaire for determining decision-making characteristics, the Childhood Narcissism Scale for determining narcissism characteristics, and the Family Relationship Scale for Children for determining family relationships. Regression analysis was used to determine whether or not students' narcissism and interfamily relations predicted their decision making characteristics, and independent samples t test was used to determine whether or not students' decision making characteristics differentiated according to gender. Results: The findings showed that narcissism characteristics of secondary school students significantly predicted self-esteem, vigilance, and complacency characteristics in decision-making. Both discouraging and supportive relations of families significantly predicted self-esteem, vigilance, complacency, panic, and cop-out characteristics in decision-making. It was also found that gender was a significant factor. Implications for Research and Practice: Both narcissism and family relations of students significantly predicted their decision making characteristics; also there were significant differences according to gender variances in decision making. The results suggest that families should be educated regarding their attitudes on raising children, and that educators and teachers should work together to support adolescents' decision-making process in a positive direction. Moreover, different studies about this issue should be conducted. (c) 2019 Ani Publishing Ltd. All rights reserved
Keywords: decision-making; narcissism; family relationship; adolescence; personality; SELF-ESTEEM; STYLES; VALIDATION; FRIENDS; PARENTS